Mouse Trmt2B protein is a dual specific mitochondrial metyltransferase responsible for m5U formation in both tRNA and rRNA. Issue 4 (2nd April 2020) - Laptev, Ivan; Shvetsova, Ekaterina; Levitskii, Sergey; Serebryakova, Marina; Rubtsova, Maria; Bogdanov, Alexey; Kamenski, Piotr; Sergiev, Petr; Dontsova, Olga
ABSTRACT: RNA molecules of all species contain modified nucleotides and particularly m 5 U residues. The vertebrate mitochondrial small subunit rRNA contains m 5 U nucleotide in a unique site. In this work we found an enzyme, TRMT2B, responsible for the formation of this nucleotide and m 5 U residues in a number of mitochondrial tRNA species. Inactivation of the Trmt2B gene leads to a reduction of the activity of respiratory chain complexes I, III and IV, containing the subunits synthesized by the mitochondrial protein synthesis apparatus. Comparative sequence analysis of m 5 U-specific RNA methyltransferases revealed an unusual evolutionary pathway of TRMT2B formation which includes consecutive substrate specificity switches from the large subunit rRNA to tRNA and then to the small subunit rRNA.